A feasibility study to evaluate the potential replication of an energy positive house in the UK. (September 2019) - Li, X; Patterson, J; Coma Bassas, E; Jones, P
Abstract: This paper presents an evaluation of the economic and technical feasibility of a renewable-led low carbon house in the UK. A holistic systems-based approach to achieve energy positive house has been taken. Long-term economic and technical feasibility analysis have been carried out based on a validated thermal and energy model of the house. The economic analysis employs the Return on Investment (ROI) method and considers changes to government financial support and technology progress over time. Results show that the extra investment on the house, compared with that for building a standard social house of similar size, can be paid back within the system lifespan under both the old Feed-in Tariff and its proposed replacement with reduced financial support. Variants examined in the technical feasibility analysis include housing type, orientation and location. Results show that the house can be replicated to achieve an energy positive performance for all variant combinations. Among the variants, location has the highest impact on building performance including annual electricity import, CO2 emission and electricity self-sufficient ratio, with South UK performing better than North UK. This implies that more efficient or advanced technologies would be needed to achieve similar building or system performance in areas of unfavourable climate. The outcome of the research has demonstrated the affordability of the energy positive house, and the technical feasibility of its replication with different housing types, orientations and locations in the UK. This study supports the wide scale replication of this affordable systems-based approach in domestic building design and construction when incorporating appropriate technologies.